Lakshmikanta : a chapter in the social history of Bengal - Ray, A. K. (Mahamandal Press, 1928)
On the life and time of Lakshmikanta Ganguli, b. 1570, a cast Brahmin born in Savarna Chowdhury family who founded the Kali Temple at Kalighat, Calcutta, and an official in Bengal Court.